Editorial: pancreatic resection in the era of laparoscopy: state of art—a systematic review - Skubleny, Daniel; Karmali, Shahzeer (Laparoscopic Surgery, 2018)
We appreciate the invitation to comment on the article “Pancreatic Resection in the era of laparoscopy: State of Art. A systematic review” published in the International Journal of Surgery (1).